The interdependence of investment by different levels of government in a federal context - Anabel Zárate Marco; Jaime Vallés Giménez (Journal of Applied Economics, 2021)
We use the Stochastic Frontier Approach to analyse for the first time the regions' investment response to the central and local governments' capital expenditure. The Spanish context is very interesting for this analysis because responsibilities are distributed between the three levels of government in a very interesting dual way: the distribution of spending responsibilities between central and regional governments corresponds to an exclusionary attribution of functions, while between regional and local levels, governments opt for cooperation. Results show that capital expenditure undertaken by the central government in the regions acts as substitute for regional investment, while capital expenditure by local governments appears to complement it. These results should be taken into account by public administrations when designing the distribution of responsibilities between different levels of government and their economic policy aims.
Keywords: 330; Decentralisation; capital expenditure; complementarity and substitution effects; frontier techniques